Difference in the Effect of Technical - Physical Exercise Combination on the Speed of 25 Free Meter Style (Crawl) Reviewed From Age Group - Ulya Mardiani; Sugiyanto Sugiyanto; M. Furqon Hidayatullah (Kazimierz Wielki University, 2019)
This study aims to determine: 1) Differences in the effect a combination of exercises, 2) Differences in swimming speed. 3) Effect interactions between combinations of exercises with age groups. This study used an experimental method with a factorial 2 x 2 design. The sample of the study was 270 people. Sampling in the study using random quota purposive sampling. The collection technique uses test and measurement techniques. Analysis of the data in this study includes a prerequisite test for the analysis and testing of hypotheses. The results of this study are: (1) There is no significant effect of the combination training method on improving swimming abilities. This can be seen from the probability value of 0.116> 0.05. (2) There is no significant difference in age categories to increase swimming ability. This can be seen from the probability value of 0.142> 0.05. (3) There are interactions between combinations of exercises with age groups. This can be seen from the probability value of 0.000